Study on The Cause of Stock Out of Logistic Installation in Harapan Kita Hospital - Hidayat, Didiet Rachmat; Simarmata, Juliater; Togas, Nelson Len (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2015)
RSAB Harapan Kita has a logistic installation as the facility of goods storage and supply, especially medical stuff (medicines) as well as non-medical ones. The focus in this research is the cause of stock out of that hospitalâs non-medical stuff. Meanwhile, to analyze thedata the author uses ishbone analysis which is also known as cause-effect analysis. The result shows ive factors causing the stock out in the installation (warehouse): the irst in the process of procurement contributing 33%, the second in the implementation of SOP contributing 27%, the third in training contributing 20%, the fourth in the coordination contributing 13%, and the last in the budget contributing 7%.